MUSLIMS’ VIEWS OF HINDU RELIGIOUS LIFE: - Nihayatul Wafiroh (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2013)
This paper discusses Banyuwangi Muslims’ perspectives and experiences when they live in Bali and how Bali with Hinduism to be the majority population influences their religious beliefs and their perspectives of interfaith relations. As data, eleven Banyuwangi Muslims were interviewed. The results are said first that hypothesis that the experiences living with other religions will contribute in their opinion of tolerance does not work hundred percentages since many of interviewees think that living in the different religious environment does not affect anything in term of their views of tolerance. Secondly, although the harmonious relations between Hindu Balinese and Banyuwangi Muslim people had existed, in reality, Hindu Balinese which are the majority population still treat differently for Banyuwangi Muslims. Indeed, it proves that the superiority cannot be truly avoided in the relations between both groups. Being minority does not always affect Banyuwangi Muslims to know the majority religion. Thirdly, the author think that it is because the main reason when they came to Bali is only economy, so everything outside economy will not be interesting for them. Living in Bali, moreover, does not contribute in their understanding of tolerance.